Umgang mit kleinen Nierentumoren im Alter = Coping with small renal tumors in the elderly - Häcker, Axel (Der Urologe, 2012)
With the continually increasing number of elderly patients and the widely distributed use of radiological imaging techniques, the number of elderly patients with incidentally discovered asymptomatic small renal tumors will increase further. Treatment options range from active surveillance, minimally invasive (ablative) techniques, to open or laparoscopic surgery including radical nephrectomy. Many studies have been published on the operative treatment of small renal tumors in the elderly; however, all are limited by the retrospective nature and the small number of cases. Chronological age per se should not be a deciding factor or even an exclusion criterion for treatment of small renal tumors. The decision for therapy should be based on the physical state (comorbidities), mental and emotional state of the patient as well as the individual psychosocial environment. The decision for surgery should be based on organ preservation, depending on the tumor size of ˂7 cm and location, whenever possible.